INNOVATIVE APPROACHES TO TEACHING ENGLISH AS A FOREIGN LANGUAGE - Vaxoboyeva Gulsanam, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article analyzes innovative approaches to teaching English, specifically focusing on the effectiveness of modern information technologies and interactive methods. The research findings demonstrate the significance of these methods in enhancing students' communicative competence.